The context of coping: a qualitative exploration of underlying inequalities that influence health services support for people living with long‐term conditions. Issue 1 (11th October 2017) - Potter, Caroline M.; Kelly, Laura; Hunter, Cheryl; Fitzpatrick, Ray; Peters, Michele
Abstract: Coping with chronic illness encapsulates both practical and emotional aspects of living life in relation to one's long‐term health condition(s). Dominant health psychology approaches for understanding coping, which underpin a more recent policy discourse on 'self‐management', focus sharply on the person affected by illness and potentially mask the influence of overarching social structure. In this paper we draw on qualitative interviews with 48 people living with long‐term conditions (LTCs), in order to highlight the role that structural configurations such as healthcare systems may play in either helping or hindering people's efforts to cope with chronic illness. We argue that coping is a social process in which health and related services, situated within their wider political‐economic contexts, play an active role in shaping people's attempts to live well with LTCs. More specifically, health systems are sites of social and cultural capital exchange that can differentially mobilise coping resources through access, continuity of care, and coordination across services. Whilst it is essential to recognise the personal agency of people living with chronic illness, it is also vital to acknowledge the underlying inequalities that affect the ways in which services can support such resourcefulness.